1983
DOI: 10.1128/jb.155.2.531-540.1983
|View full text |Cite
|
Sign up to set email alerts
|

Amplifiable resistance to tetracycline, chloramphenicol, and other antibiotics in Escherichia coli: involvement of a non-plasmid-determined efflux of tetracycline

Abstract: Increasing levels of resistance to tetracycline and to a number of other unrelated antibiotics, including chloramphenicol, beta-lactams, puromycin, and nalidixic acid, occurred in Escherichia coli after 50 to 200 generations of growth in the presence of subinhibitory concentrations of tetracycline or chloramphenicol. In the absence of selective pressure, resistances fell to low levels within 100 generations of growth. This amplification of resistance was observed in laboratory and naturally occurring E. coli s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
3

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(152 citation statements)
references
References 35 publications
2
147
0
3
Order By: Relevance
“…Induction of the mar operon is of considerable significance to the food industry. Cells with an induced mar operon display increased tolerance to a vari-ety of inimical substances (George and Levy 1983;Greenberg et al 1991;White et al 1997), potentially making cells more difficult to eliminate from food production environments. Thus, as demonstrated, a mild induction of rpoS may have a significant impact on processes related to survival in the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of the mar operon is of considerable significance to the food industry. Cells with an induced mar operon display increased tolerance to a vari-ety of inimical substances (George and Levy 1983;Greenberg et al 1991;White et al 1997), potentially making cells more difficult to eliminate from food production environments. Thus, as demonstrated, a mild induction of rpoS may have a significant impact on processes related to survival in the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…3.3.1 Efflux pumps and antimicrobial resistance. Sublethal concentrations of antibiotics and biocides might act as inducers/transcriptional activators of more tolerant phenotypes, such as those expressing the multidrug resistance operon mar and efflux pumps such as acrAB (George and Levy 1983;Ma et al 1993). Activators of mar include subeffective concentrations of antibiotics (tetracycline and chloramphenicol), biocides (QACs, triclosan and pine oil) and xenobiotics such as salicylate.…”
Section: Resistance Associated With the Adoption Of Resistance Phenotmentioning
confidence: 99%
“…This finding suggested that a basal level of intrinsic resistance was present in wild-type strains. Mar mutants exhibited efflux of tetracycline [15], chloramphenicol [32], and norfloxacin [33]. The sequenced mar locus consists of two divergent transcriptional units expressed from a central operator/promoter region (mar-01 that contains two sets of direct repeats [14].…”
Section: Soxs Is An Activator Of Superoxide Stress Genes In E Colimentioning
confidence: 99%
“…Mar mutants of E. coli selected by low concentra-Alleles that affect the Mar phenotype are found tions of tetracycline or chloramphenicol express only in marR or marA [ 14,371, and the overexprescross-resistance to many structurally and functionally sion of MarA alone is sufficient to confer a Mar unrelated antibiotics, and continuous contact with the phenotype [37]. Roles for marB, and marC which is selecting drug caused mutants to attain very high divergently transcribed from the mar0 region, have levels of resistance to these antibiotics [ 15,161. This yet to be determined.…”
Section: Soxs Is An Activator Of Superoxide Stress Genes In E Colimentioning
confidence: 99%